2022
DOI: 10.1111/1468-0009.12562
|View full text |Cite
|
Sign up to set email alerts
|

Financing Approaches to Social Prescribing Programs in England and the United States

Abstract: The number of social prescribing practices, which aim to link patients with nonmedical services and supports to address patients' social needs, is increasing in both England and the United States.r Traditional health care financing mechanisms were not designed to support social prescribing practices, and flexible payment approaches may not support their widespread adoption.r Policymakers in both countries are shifting toward developing explicit financing streams for social prescribing programs. Consequently, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 84 publications
1
29
0
Order By: Relevance
“…Financing approaches for social prescribing approaches vary across countries. 44 Existing studies and our interview data showed that implementation of social prescribing may not require new funds if health systems are able to repurpose existing staff and infrastructure (Portugal, Canada, Netherlands, Spain, Japan). 10 18 21 However, many programmes do require additional funding, for salaries, management and infrastructure.…”
Section: Financing Community Organisations and Societal Partnershipsmentioning
confidence: 78%
“…Financing approaches for social prescribing approaches vary across countries. 44 Existing studies and our interview data showed that implementation of social prescribing may not require new funds if health systems are able to repurpose existing staff and infrastructure (Portugal, Canada, Netherlands, Spain, Japan). 10 18 21 However, many programmes do require additional funding, for salaries, management and infrastructure.…”
Section: Financing Community Organisations and Societal Partnershipsmentioning
confidence: 78%
“…[80] The outputs of this work help to clarify these core components of social prescribing, with the operational definition providing the clearest example of this -Condition 2 is the stage at which the social prescription occurs when the identifier is the social prescriber, whereas Condition 4 is the stage at which the social prescription occurs when the connector is the social prescriber. Additionally, the outputs of this work reflect current understanding of key facets of social prescribing, such as the holistic approach, [7,11] the central role that is played by identifying non-medical, health-related social needs and subsequently connecting to non-clinical supports and services within the community, [80,81] the linkages to improving health and wellbeing [1,7,11] and to strengthening community connections, [82] the responsibilities of the connector, [7,11,12,30,81] and the importance of monitoring and evaluation. [11,12,30] From a global health standpoint, Morse et al [1] highlight that social prescribing links to multiple trends in global health care, many of which are found in the outputs of this work, such as person-centredness, co-production, and health promotion.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that it would not require many more resources to start with a pragmatic approach. A sustainable and established implementation of improved cooperation between primary care and social care probably requires pooled financing initiatives [73].…”
Section: Strengths and Weaknessesmentioning
confidence: 99%